2019
DOI: 10.1136/injuryprev-2019-043544
|View full text |Cite|
|
Sign up to set email alerts
|

Average medical cost of fatal and non-fatal injuries by type in the USA

Abstract: ObjectiveTo estimate the average medical care cost of fatal and non-fatal injuries in the USA comprehensively by injury type.MethodsThe attributable cost of injuries was estimated by mechanism (eg, fall), intent (eg, unintentional), body region (eg, head and neck) and nature of injury (eg, fracture) among patients injured from 1 October 2014 to 30 September 2015. The cost of fatal injuries was the multivariable regression-adjusted average among patients who died in hospital emergency departments (EDs) or inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
0
21
0
2
Order By: Relevance
“…CCR was estimated for ED records (mean: 0.385, data not shown) by matching HCUP-NEDS hospital characteristics to HCUP-NIS CCR data. 10 PFR estimates in the reference source were based on insurance payments to physicians relative to facility payments in medical claims data. 11 PFR was assigned by encounter type and primary payer for this analysis: ED (Medicaid or Medicare, 1.440; all other payers, 1.286) or inpatient (Medicaid or Medicare, 1.177; all other payers, 1.264).…”
Section: Methodsmentioning
confidence: 99%
“…CCR was estimated for ED records (mean: 0.385, data not shown) by matching HCUP-NEDS hospital characteristics to HCUP-NIS CCR data. 10 PFR estimates in the reference source were based on insurance payments to physicians relative to facility payments in medical claims data. 11 PFR was assigned by encounter type and primary payer for this analysis: ED (Medicaid or Medicare, 1.440; all other payers, 1.286) or inpatient (Medicaid or Medicare, 1.177; all other payers, 1.264).…”
Section: Methodsmentioning
confidence: 99%
“…Sample selection of patients with non-fatal emergency department–treated injuries in MarketScan, 1 October 2014 through 30 September 2015. a Patients age 18–64 years with commercial health insurance are a subset of the injury patient sample described in Peterson, Xu, Florence (2019) 19 . b Absences by type are reported separately in MarketScan Health and Productivity Management database and enrollee eligibility for each absence type reporting is independent—meaning, an enrollee could be eligible for short-term disability and workers’ compensation absence reporting but not workplace absences (eg, annual leave)—and therefore analysis of each absence type comprised separate enrollee samples.…”
Section: Methodsmentioning
confidence: 99%
“…Patients admitted as inpatients following the ED index visit were identified by an admission (ie, MarketScan Inpatient Admissions database) on the day of or day following the index visit. The sample of injury patients identified in this way was recently used to estimate the average medical cost of injuries by type 19. Among that sample, for this study, authors identified injury patients aged 18–64 years with employer health insurance who had reported workplace absence data (or, ‘eligibility’ for such reporting—an important distinction because enrollees can have zero reported absences for a given period) in MarketScan HPM for 12 months beginning with patients’ ED index visit (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…A kórházi ellátásra szoruló térd-és lábszársérülést szenvedőknek a kórházat elhagyva általában további, akár éveken át tartó gondozásra, kezelésre is szükségük lehet. A hosszas ápolási és rehabilitációs idő mind a fiatal, mind az időskorú lakosság tekintetében további költségeket generálhat [3,21,35,36]. A járóbeteg-szakellátási forma esetében az előző évben műtéten átesett betegek is bejelentésre kerülhetnek, ezért vizsgálatunkban az aktívfekvőbeteg-szakellátás betegforgalmi és egészségbiztosítási adatait tekintettük meghatározónak.…”
Section: Megbeszélésunclassified